Making the connections between academic work and learning analytics : A framework for driving learning analytics take up. - West, Deborah (HERDSA Review of Higher Education v.6 p.65-89, 2019)
Developments in the field of learning analytics have heralded the promise of new insights into the learning and teaching for some years now (Mazza and Milani, 2004; Romero, Ventura, & Garcia, 2008). Responding to a range of drivers in the field, the sector took up the challenge of applying emerging data science techniques. Early work focussed on the issue of student retention but has moved to a broader focus on student success opening up a myriad of opportunities to improve the learning and teaching experience. Yet, despite the field making substantial progress in relation to analytics techniques, the translation of this into practice has been somewhat limited. A key challenge to translation into practice has been the take up of learning analytics across institutions by those most connected to the teaching - academics. While many people in institutions have a role to play in supporting students and moving learning analytics forward, academics are pivotal as they are central to the curriculum, the teaching and in relationship to students. This review provides a background to developments in the field focussing on the connections between learning analytics and academics highlighting the key challenge that we face as we work to increase the take up and application of learning analytics. In order to move forward connections need to be made between academic work and learning analytics. This is presented in a framework for driving learning analytics take up including the connections to the purpose of various reports and learning and teaching lifecycles. [Author abstract]